Comparative outcomes of two competitive devices for retrograde closure of perimembranous ventricular septal defects - Haddad, Raymond N.; Saliba, Zakhia S. (Frontiers in Cardiovascular Medicine, 2023)
Background: Retrograde closure of perimembranous ventricular septal defects (pmVSDs) is a well-established procedure. However, interventionists are still looking for the best closure device. Methods: We performed a single-center retrospective review of 5-year-experience (from July 2015 to July 2020) with retrograde closure of pmVSDs using AmplatzerTM Duct Occluder II (ADOII) and KONAR-MF™ VSD occluder (MFO). Deficient sub-aortic rim (SAR) (≤2.5 mm for MFO and ≤3 mm for ADOII) was an exclusion criterion in defects with a diameter ratio (right-side exit/left-side entry) > 0.5. Results: We identified 77 patients (57.1% males) with a median age of 4.3 years (IQR, 2.2-8.3) and a median weight of 16 kg (IQR, 11.2-24.5). 44 (57.1%) defects (22.7% with deficient SARs) with a median left-side defect diameter of 8.7 mm (IQR, 5.7-10) were closed with ADOIIs. 33 (42.9%) defects (51.5% with deficient SARs) with a median left-side defect diameter of 10.8 mm (IQR, 8.8-13.5) were closed with MFOs. One 7/5 MFO was removed before release and upsized to a 12/10 MFO. Implantation success rate was 100% with ADOII and 90.9% with MFO devices. Two MFOs were snare-recaptured after embolization, and one 9/7 MFO was snare-retrieved for a new onset of grade-2 aortic regurgitation that persisted afterward. Median follow-up was 3.3 years (IQR, 2.1-4.2) for ADOII and 2.3 years (IQR, 1.7-2.5) for MFO. No permanent heart block or death occurred. Freedom from left ventricular dilation was 94.62% at 36 months of follow-up. Freedom from residual shunt was 90.62% for MFO and 89.61% for ADOII at 24 months of follow-up. One 2.6-year-old patient with baseline mild aortic valve prolapse and trivial aortic regurgitation developed a grade-2 aortic regurgitation after 9/7 MFO implantation. He was treated surgically after two years without device extraction. One new grade-2 asymptomatic tricuspid regurgitation persisted at the last follow-up in the ADOII group. Conclusions: ADOII and MFO are complementary devices for effective retrograde closure of pmVSDs in children, including defects with absent or deficient SAR. ADOII is limited to smaller defects but offers a lower profile and a flexible left-side disk for better maneuverability over the aortic valve during retrograde implantation.